Nutritional balance analysis for productivity improvement of rice in iron rich Lateritic Alluvium - Bridgit T K (Department of Agronomy, College of Horticulture, 1999)
Investigation entitled “Nutritional balance analysis for productivity improvement of rice in iron rich lateritic alluvium” consisting of seven experiments was conducted during 1995-1997 in the farm attached to the Agricultural Research Station, Mannuthy. Objective of the study was to identify the factors that limit the productivity of rice in the lateritic alluvium, estimate the nature and extent of their influences, formulate and test the methodology to overcome them and to evolve high – tech management programme to get 6 t or more yield of grain per hectare. The study included evaluation of the influences of all the cultural and nutritional inputs on the content and balances of N,P,K,Ca,Mg,S,Fe,Mn,Zn, Cu and SiO2 in the root, culm and leaf at MT and PI and boot leaf in addition to uptake in grain and straw. Results revealed the following Field evaluation of the crop performance in 36 locations of Thrissur and Palakkad districts of Kerala spread in km2 and three soil types revealed that yield ranged from 2800 to 9000 kg ha-1. Low productivity was not due to real deficiency of any of the 11 elements in the foliage. Foliar concentrations of individual elements were more than what has required to produce yield levels above 7000kg ha-1 in some locations expect for silica. Low realized yields were found to be due to the excess plant contents of non-applied elements especially Fe, Mn,Zn and Cu as well as their interactions in plants. As such, soil test or tissue test values of elements were found inadequate, a “content balance combined approach” was found to be better tool in nutritional management. Iron content of the root of the order of 50,000 ppm under submerged conditions was found to inhibit morphological and physiological development leading to low yield. Physiologically, lower development of chlorophyll ‘a’ and its poor stability as well as a higher sap PH lead to low dry matter accumulation. Morphologically the effect was expressed through very few long roots at MT,low root weight, root damage and failure of further initiation of roots, protracted production of fewer tillers as well as their decline and low dry matter accumulation in the shoots between MT and flowering periods. Yield variation due to the early suppression alone was of the order of 1800 kg ha-1. Harmful effects of Fe in the plant was less subsequently as Fe decreased progressively with growth of the plant. Manganese and Zn and to some extent Cu found to take over from Fe in the post panicle initiation phase. Leaf concentrations of these elements at PI and flowering stages rise far higher the critical levels. Manganese was found to reduce photosynthetic efficiency at this stage and Zn was identified with affecting translocation to the grain from vegetative parts in the maturity phase, thereby affecting translocation to the grain from vegetative parts in the maturity phase, thereby affecting grain – straw ratio. Lower productivity of second crop (September – October compared to first crop (April – May seeded rice) was found to be due to the higher foliar concentrations of Mn and Zn in the PI stage onwards. Cultivation under continuous submergence aggravated these inhibiting influences. Thus low yield of rice in laterite soils was found to be due to a multi – element multiphase effect. Nutritionally these effects could be recognised through narrow N/Fe, N/Mn, K/Fe, K/Zn ratios. Application of Ca @ 150 kg lime ha-1 could reduce the Fe content of the plant and S at 100 kg ha-1 could reduce Mn and Zn content in the plant at PI. Substituting urea with Ammonium sulphate for top dressing appeared to be better to contain Mn and Zn at PI stage. Application of SiO2 at 250 kg ha-1 and increasing the levels of K from the present level of 45 kg to 120 kg ha-1 and resorting to dry seeding in April-May crop and wet seeding in October-crop and irrigation once in three days after disappearance of ponded water were found to be effective means of containing the low yield malady and raise the yield beyond 6 t ha-1. This production programme has the advantage that it does not involve much additional input, offers the scope of reducing P application by 50 per cent and scientifically sustainable as it keeps nutrient removal within the levels of application of N, P and K. This programme also offers a way to progressional yield improvement above 6 t ha-1 as the levels of Fe, Mn and Zn in the leaves are still far higher than suggested critical levels.